PENERAPAN ALGORITMA STEEPEST ASCENT HILL CLIMBING (SAHC) DALAM APLIKASI MOBILE UNTUK PENCARIAN RUTE TERPENDEK - Siti Khairunnisa Siregar (ADISAM PUBLISHER, 2025)
Finding the shortest route is a problem that is often discussed in artificial intelligence technology. This research implements the Steepest Ascent Hill Climbing (SAHC) algorithm for a mobile-based shortest route search application in Humbang Hasundutan Regency. This algorithm was chosen because of its ability to find optimal solutions using the best heuristic values. The research results show that the SAHC algorithm is able to find the shortest route from the Sipinsur Geosite to Simolap Waterfall with a total distance of 51 km and a travel time of 1 hour 34 minutes. Algorithm implementation was carried out using Android Studio with the Java programming language. It is hoped that this research can contribute to the development of mobile-based applications to support the tourism sector.